2019
DOI: 10.1038/s41598-018-37659-4
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of fullerene aggregation on lipid saturation due to a balance between entropy and enthalpy

Abstract: It is well-known that fullerenes aggregate inside lipid membranes and that increasing the concentration may lead to (lethal) membrane rupture. It is not known, however, how aggregation and rupture depend on the lipid type, what physical mechanisms control this behavior and what experimental signatures detect such changes in membranes. In this paper, we attempt to answer these questions with molecular simulations, and we show that aggregation and membrane damage depend critically on the degree of saturation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 70 publications
4
22
0
Order By: Relevance
“…The optimized simulation protocols had been intensively tested 73,74 and extensively used. [75][76][77][78] Molecular visualizations were done using the Visual Molecular Dynamics (VMD) soware. 79 Translocation free energy.…”
Section: Methodsmentioning
confidence: 99%
“…The optimized simulation protocols had been intensively tested 73,74 and extensively used. [75][76][77][78] Molecular visualizations were done using the Visual Molecular Dynamics (VMD) soware. 79 Translocation free energy.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, most computational studies of fullerenes in lipid membranes deal with single component lipid bilayers. Our previous computational studies [24] show that fullerene aggregation and its physical mechanisms depend on the degree of lipid unsaturation. Open questions include if the position(s) and the number of double bonds are important in fullerene-lipid interactions.…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies [22,24] show that fullerenes neither aggregate inside lipid bilayers nor cause physical damage. On the other hand, at high concentrations several experimental and computational studies have shown that fullerenes aggregate and may be harmful to biological membranes [24][25][26][27][28][29][30][31]. Even the deceivingly simple question of whether fullerenes aggregate inside membranes remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…† The RDFs are found to be in reasonable agreement with previous studies. 39,66 The relative distances of pristine fullerenes have been determined to be similar in all membrane types despite the variations in peak intensities. For example, the peak around 1.05 nm is observed to have higher intensity in peroxidized membranes particularly in DOBU30 and POBU70 than regular DOPC or POPC.…”
Section: Resultsmentioning
confidence: 95%
“…31,32 Previous computational studies covered the permeation of monomeric fullerene across a lipid bilayer, 33 solvation of fullerene in water, 34 interactions of fullerene dimers inside a bilayer, 35 effects of fullerene on liquid ordering, 36 and fullerene aggregation on lipid membranes. [37][38][39] To our knowledge, however, no study to date has examined the interactions of fullerene molecules with peroxidized lipid membranes, which is a so-called indicator of toxicity. This work provides an insight into the fullerene permeation across lipid membranes depending on the concentration and polarity of fullerene as well as the level of peroxidation of bilayers and suggests that the peroxidation is not likely the cause of membrane integrity disruption in the toxicity mechanism of fullerenes at the concentration levels tested.…”
Section: Introductionmentioning
confidence: 99%